2014
DOI: 10.1002/ece3.1048
|View full text |Cite
|
Sign up to set email alerts
|

Predicting future coexistence in a North American ant community

Abstract: Global climate change will remodel ecological communities worldwide. However, as a consequence of biotic interactions, communities may respond to climate change in idiosyncratic ways. This makes predictive models that incorporate biotic interactions necessary. We show how such models can be constructed based on empirical studies in combination with predictions or assumptions regarding the abiotic consequences of climate change. Specifically, we consider a well-studied ant community in North America. First, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 85 publications
(211 reference statements)
0
9
0
Order By: Relevance
“…We found support for this based on a comparison of CT max and activity season among six species from a single site in North Carolina: species whose foragers had a higher CT max were active for a shorter period of the year. A previous study also found that A. rudis had a relatively long activity season compared with two other co-occurring species (Bewick et al 2014).…”
Section: T H E R M a L S T R A T E G I E S I N A N T S A N D E C O L mentioning
confidence: 77%
See 1 more Smart Citation
“…We found support for this based on a comparison of CT max and activity season among six species from a single site in North Carolina: species whose foragers had a higher CT max were active for a shorter period of the year. A previous study also found that A. rudis had a relatively long activity season compared with two other co-occurring species (Bewick et al 2014).…”
Section: T H E R M a L S T R A T E G I E S I N A N T S A N D E C O L mentioning
confidence: 77%
“…A previous study also found that A. rudis had a relatively long activity season compared with two other co‐occurring species (Bewick et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…At the location scale, the net effect of competition (Basset & Rossi, ; Lawlor, ) was to increase species assemblage stability, mitigating the negative effect of habitat degradation. Indirect responses mediated by species interactions have the potential to exceed the direct effect of environmental changes at both population and community levels, leading to disturbance propagation or attenuation within the community (Bewick et al., ; Montoya et al., ). Here, the net effect of species interactions was to reverse the outcomes of competition on population dynamics and stabilize communities (Lawlor, ; Montoya et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Further work investigating the variation in genomic content and mapping of target coding regions from previous physiological (Nguyen et al, 2017), biochemical (Helms Cahan et al, 2017), and transcriptomic (Stanton-Geddes et al, 2016) studies of Aphaenogaster and other ant species will inform predictions of how these species, and the ecosystems that they inhabit, may respond to ongoing climatic change. For instance, determining the genomic factors underlying the temperature response of ant assemblages to climatic gradients (Warren and Chick, 2013; Diamond et al, 2016, 2017) could provide useful insights into the response of these important organisms to non-analog ecosystem states and idiosyncratic community responses (Bewick et al, 2014). In addition, as species distribution models have been significantly improved by the inclusion of genetic information (Ikeda et al, 2016), an ecological genetics approach that couples ant genomic and ecologically relevant data will provide a useful window into the response of many terrestrial ecosystems to a changing climate.…”
Section: Resultsmentioning
confidence: 99%